2012
DOI: 10.1371/journal.pone.0032556
|View full text |Cite
|
Sign up to set email alerts
|

Expression of High-Affinity IgE Receptor on Human Peripheral Blood Dendritic Cells in Children

Abstract: BackgroundIn a mouse model of viral induced atopic disease, expression of FcεRI on dendritic cells is critical. While adult human conventional (cDC) and plasmacytoid (pDC) dendritic cells have been shown to express FcεRI, it is not known if this receptor is expressed in childhood and how its expression is governed by IgE.MethodsFollowing informed consent of subjects (n = 27, aged 12–188 months), peripheral blood was stained for surface expression of CD19, ILT7, CD1c, IgE, FcεRI and analyzed by flow cytometry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 25 publications
(36 reference statements)
1
28
0
Order By: Relevance
“…Moreover, since it is well-known that FcεRI is present not only on mast cells but also on basophils, eosinophils, neutrophils, monocytes, and on different subsets of dendritic cells [43], it may be assumed that IgE may regulate the response of other FcεRI-bearing cells. Indeed, recent studies have indicated that some cellular activities of basophils and dendritic cells are modulated by IgE molecules [44], [45]. Undoubtedly, the repertoire of biological effects elicited by IgE needs to be further clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, since it is well-known that FcεRI is present not only on mast cells but also on basophils, eosinophils, neutrophils, monocytes, and on different subsets of dendritic cells [43], it may be assumed that IgE may regulate the response of other FcεRI-bearing cells. Indeed, recent studies have indicated that some cellular activities of basophils and dendritic cells are modulated by IgE molecules [44], [45]. Undoubtedly, the repertoire of biological effects elicited by IgE needs to be further clarified.…”
Section: Discussionmentioning
confidence: 99%
“…This translation is just beginning, but it has been shown that the high-affinity IgE receptor is found on human DCs in peripheral blood samples from children as early as one year of age (111). Analysis of the second immune axis is challenging due to the rarity of NKT cells and the need for specific biomarkers of M2 macrophages in lung tissue.…”
Section: Innate Immune Cells and Viral Diseasementioning
confidence: 99%
“…However, whether FcεRI on DCs and monocytes is also stabilized by IgE binding is not clearly established. Some studies have shown that surface FcεRI of human blood BDCA1 + DCs and monocytes correlates positively with serum IgE levels (20,21). However, other studies have shown a lack of correlation between IgE levels in blood and FcεRI levels on BDCA1 + DCs or monocytes among individuals with normal ranges of serum IgE levels (8,22).…”
Section: Introductionmentioning
confidence: 99%